A regionális együttműködés kudarca, avagy a horvát-szlovén határvita - Lőrinczné Bencze, Edit (Közép-Európai Közlemények, 2011)
During the era of the socialist Yugoslavia, the border was between two republics within a united Yugoslav federal entity, however after the disintegration drawing borders –maritime and land ones –between two newly independent countries has lots of debates and difficulties. The paper discusses the impact of the international border established in 1991 on cross-border between Croatia and Slovenia. In the first part it will be presented the factual context of the dispute, followed by a presentation of the legal arguments that both countries have laid on the table so far. The papers shows the most hotly contested three land-border disputes between the two countries, but he focal point of this essay will be a legal assessment or a legal prediction of the outcome of the maritime border delimitation dispute between Slovenia and Croatia in the northernmost part of the Adriatic Sea, namely in the Piran Bay. The paper highlights the effect of the border dispute on the accession of Republic of Croatia into the European Union. Finally, the paper attempts to indicate the future development of the area in the context of European Union and summaries of the main reasons of the dispute, having not only geopolitical, but also nation-building, identical, economical aspects.